Influencing Factors of International Students’ Anxiety Under Online Learning During the COVID-19 Pandemic: A Cross-Sectional Study of 1,090 Chinese International Students - Tan, Yejun; Wu, Zhijian; Qu, Xiangnan; Liu, Yuzhuo; Peng, Lele; Ge, Yan; Li, Shu; Du, Jinfeng; Tang, Qi; Wang, Jia; Peng, Xiaofei; Liao, Jiafen; et al. (Frontiers in Psychology, 2022)
Objective We conducted the following cross-sectional study to comprehensively assess the anxiety among Chinese international students who studied online during the COVID-19 pandemic and its influencing factors. Methods Questionnaires were distributed through “Sojump,” and a total of 1,090 valid questionnaires were collected. The questionnaire was divided into two parts: general situation and anxiety assessment of students. The former used a self-made questionnaire, and the international general GAD-7 scale was used to measure anxiety. Chi-square test was used to analyze the differences between groups, and logistic regression analysis was performed for the factors with differences. Results Anxiety was found in 707 (64.9%) of 1,090 international students. Chi-square test and multivariate Logistic regression analysis showed that the incidence of anxiety was higher in the group under 22 years of age than in the group over 22 years of age (68% vs. 61%, p = 0.015; OR = 1.186, 95% CI 1.045–1.347, p = 0.008); International students living in big cities had a higher incidence of anxiety than those living in rural areas (67% vs. 60%, p = 0.022; OR = 1.419, 95%CI 1.038–1.859, p = 0.011); international students who socialized 3 times or less monthly had a higher incidence of anxiety than those who socialized more than 3 times per month (68% vs. 58%, p = 0.003; OR = 1.52, 95%CI 1.160–1.992, p = 0.002); international students who expected purely online teaching had a higher incidence of anxiety than those who expected purely offline teaching or dual-track teaching (72% vs. 64%, p = 0.037; OR = 1.525, 95%CI 1.069–2.177, p = 0.02); international students with a subjective score of online learning experience of 6 or less had a higher incidence of anxiety than those with subjective scores of more than 6 (70% vs. 60%, p = 0.001, OR = 1.25, 95%CI 1.099–1.422, p = 0.001). However, gender, emotional status, BMI, major of study, vaccination status, and degree type had no significant difference in the incidence of anxiety among international students who studied online during the COVID-19 pandemic. Conclusion During COVID-19, international students who were younger, came from big cities, had low social frequency, expected purely online teaching, and had poor experience of online classes were risk factors for anxiety during online classes.